ESTIMATION OF METAL CONTENT IN AVIAN FAUNA OF SIALKOT, PAKISTAN USING FEATHERS AS BIO-INDICATOR - A. Shehzad; K. M. Anjum; A. Yaqub; S. Zahid; M. Z. Yousaf; N. Khan; M. Yaseen; A. Habib (Journal of Animal and Plant Sciences, 2022)
The intent of the present study was to determine the concentrations of metal content in feather samples of different avian species collected from different areas of Sialkot, Pakistan. For this purpose atomic absorption spectrophotometer was used to estimation the metals concentration. The estimated concentration (µg/g) of these metals were 104.89±22.39, 23.19±1.23, 15.68±3.50, 10.18±2.47, 5.38±1.50, 1.52±0.02 for Zinc> lead> chromium> copper> nickel> cadmium respectively. The concentration of cadmium was found to be lower than the threshold level. However, continuous exposer to metals may result in the bio-magnification of metals in body especially in soft tissues such as liver, kidneys which is harmful for avian fauna. The concentrations of lead and chromium in the feather samples were found to be more than the approved /required levels of these minerals may be the one reason for the decline of avian fauna in study area. The main sources of metal pollution are the tanneries and surgical industries in study area as these industries use lead, chromium and zinc salts extensively. Most of these industries dispose of their untreated waste water in the naturel water resources such as in river and canals threatening to the aquatic flora and fauna. Results of the present study revealed that feathers may be used as bio-indicator for estimation of environmental pollution. The findings will also highlight the threats to the ecology and diversified avian fauna of the study area.
Keywords: Avian fauna; Bio-indicator; Environmental pollution; Feathers; Metal contents